Effective leadership theory, cases, and applications - Humphrey, Ronald H. (SAGE Publications, Inc., 2014)
Intorduction - Traits and characteristics of leaders - Adaptive leadership approaches - How leaders motivate themselves and others - Concluding thoughts.